Racism and the Incorporation of Foreign Labour: Farm Labour Migration to Canada Since 1945 - Satzewich, Vic (Critical studies in racism and migration, 1991)
Intended to be of interest to students of sociology, ethnic studies and history, this book assesses the political economy of migration. Labour shortages, the racialization of Caribbean migrant farm labour and alternatives to labour imports are discussed. --Publisher's description
Keywords: Agricultural laborers, Foreign; Agricultural laborers, Foreign Canada History; Boeren; Buitenlandse arbeiders; Canada; Canada Relations raciales Histoire; Children of foreign workers; Children of foreign workers Canada History; Discrimination raciale Canada Histoire; Einwanderung; Enfants de travailleurs étrangers Canada Histoire; Foreign workers; Foreign workers Canada History; Foreign workers, West Indian; Foreign workers, West Indian Canada History; Geschichte 1945-1990; History; Kanada; Landarbeiter; Migratie (demografie); Personnel Immigrants; Race discrimination; Race discrimination Canada History; Racism; Rassendiscriminatie; Travailleurs agricoles étrangers Canada Histoire; Travailleurs étrangers Canada Histoire; Travailleurs étrangers antillais Canada Histoire